2015
DOI: 10.1186/s12889-015-2284-2
|View full text |Cite
|
Sign up to set email alerts
|

Is population structure sufficient to generate area-level inequalities in influenza rates? An examination using agent-based models

Abstract: BackgroundIn New Haven County, CT (NHC), influenza hospitalization rates have been shown to increase with census tract poverty in multiple influenza seasons. Though multiple factors have been hypothesized to cause these inequalities, including population structure, differential vaccine uptake, and differential access to healthcare, the impact of each in generating observed inequalities remains unknown. We can design interventions targeting factors with the greatest explanatory power if we quantify the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
0
30
0
2
Order By: Relevance
“…Hospitalizations in the US among children and adults for seasonal influenza and 2009 H1N1 were found to increase with poverty 13,15,18,147 . A model of influenza spread that incorporated increasing susceptibility with decreasing SES closely matched the increased early influenza rate in high-poverty census tracts observed during the 2009 H1N1 pandemic 148 . Modeled influenza spread in Delhi demonstrated that, by ignoring the attributes of slums (lower income, crowding, etc.)…”
Section: Socioeconomic Status (Ses) As a Health Risk Factormentioning
confidence: 72%
“…Hospitalizations in the US among children and adults for seasonal influenza and 2009 H1N1 were found to increase with poverty 13,15,18,147 . A model of influenza spread that incorporated increasing susceptibility with decreasing SES closely matched the increased early influenza rate in high-poverty census tracts observed during the 2009 H1N1 pandemic 148 . Modeled influenza spread in Delhi demonstrated that, by ignoring the attributes of slums (lower income, crowding, etc.)…”
Section: Socioeconomic Status (Ses) As a Health Risk Factormentioning
confidence: 72%
“…A similar result was reported in Kumar et al . 11 This outcome can be explained by the fact that when viral transmission is very high, as in the case of catastrophic influenza, the higher contact rates and other characteristics of 13% of individuals in the network do not matter as much. The high transmission rate dominates the impact arising from changes in the network structure.…”
Section: Resultsmentioning
confidence: 99%
“…In the US, counties in 14 states show correlation between higher census tract-level poverty with higher influenza-related hospitalisation. 8 9 Yousey-Hindes and Hadler 10 find mean annual incidence of paediatric influenza-based hospitalisation in high-poverty and high-density areas to be at least three times higher in New Haven, Connecticut whereas Kumar et al 11 detect a steeper, earlier influenza rate increase in high-poverty census tracts in New Haven.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst much attention has been given to investigating the impact of transmission heterogeneity on the overall effectiveness of control strategies [ 41 , 42 ], we build on this work by considering the role of heterogeneity in influencing inequalities in infectious disease outcomes, rather than the overall disease burden. Transmission models have previously been developed to evaluate the impact of social structure on observed inequalities in reported incidence of pandemic and seasonal influenza [ 43 , 44 ]. By using socio-economic census data, these studies can replicate some of the location-specific inequalities between pre-defined social groups.…”
Section: Discussionmentioning
confidence: 99%